Інтелектуальний аналіз і обробка вимірювальної інформації в підсистемі технологічного моніторингу процесу екстрагування цукру - Зігунов, О. М.; Кишенько, В. Д. (Видавництво Львівської політехніки, 2011)
A general description of the subsystem for monitoring of sugar factory diffusion technological department, the main stages of processing, evaluation of the management object through data mining (clearing signal, wavelet analysis, forecasting).
Keywords: process monitoring subsystem; intelligent analysis; data processing